(untitled) (Journal of the College of Basic Education, 2022)
This work involves the preparation of three phenol-formaldehyde resins that have pendant 1-cyclopentene-1,2-dicarboxylimidyl.The target compounds produce by condensation of N-(hydroxyl phenyl)-1-cyclo pentene-1,2-dicarboxylimidyl with formaldehyde under conditions similar to those in Novolac preparation. The prepared resins were modified by esterification of phenolic hydroxyl groups in the prepared resins via treatment with benzoyl, acryloyl, methacryloyl and cinnamoyl chlorides respectively in the presence of triethylamine. The synthesis compounds were characterized by FTIR and U.V spectral data and determined softening points of crystalline solid resins, intrinsic viscosities of soluble resins